EVALUASI KEBIJAKAN PERDA KOTA BATAM NOMOR 5 TAHUN 2013 TENTANG PENCEGAHAN DAN PENANGANAN KORBAN PERDAGANGAN ORANG - Linda, Agnesia; Harma, Ulima (LPPM Universitas Putera Batam, 2019)
Indonesia is the fourth largest country with a population of 295 million. As a developing country, Indonesia also has global problems. One of them is the problem of human trafficking. Human trafficking is a crime that is truly embarrassing and threatens human existence, as cultured beings we must eradicate together by building synergistic strength between various components and elements of society at all levels (local, regional, national, and global) simultaneously. In Indonesia, especially the Riau Islands Province in Batam City is a city with free trade routes. Its strategic location makes Batam City a transit city for victims of trafficking from domestic and abroad. This research was conducted so that the Batam City Government and all citizens, could play an active role in preventing and handling victims. It is hoped that researchers for the City of Batam will be free from acts of human trafficking and become safe, prosperous cities.